Saša Stanišić: Poetologie und Werkpolitik - Meister, Amelie; Holweck, Katja (De Gruyter, 2023)
Saša Stanišić is one of the most important voices in contemporary German literature. This volume reveals new perspectives on Stanišić's work and his authorial persona. It focuses on previously neglected aspects, such as Stanišić's early prose, his online writing, practices of authorial staging, and the work he has done on the canon. It thus provides stimuli for further differentiation in scholarly discussions about the author and his texts.